Cadherin-6 is a putative tumor suppressor and target of epigenetically dysregulated miR-429 in cholangiocarcinoma. Issue 11 (1st November 2016) - Goeppert, Benjamin; Ernst, Christina; Baer, Constance; Roessler, Stephanie; Renner, Marcus; Mehrabi, Arianeb; Hafezi, Mohammadreza; Pathil, Anita; Warth, Arne; Stenzinger, Albrecht; Weichert, Wilko; Bähr, Marion; et al.
ABSTRACT: Cholangiocarcinoma (CC) is a rare malignancy of the extrahepatic or intrahepatic biliary tract with an outstanding poor prognosis. Non-surgical therapeutic regimens result in minimally improved survival of CC patients. Global genomic analyses identified a few recurrently mutated genes, some of them in genes involved in epigenetic patterning. In a previous study, we demonstrated global DNA methylation changes in CC, indicating major contribution of epigenetic alterations to cholangiocarcinogenesis. Here, we aimed at the identification and characterization of CC-related, differentially methylated regions (DMRs) in potential microRNA promoters and of genes targeted by identified microRNAs. Twenty-seven hypermethylated and 13 hypomethylated potential promoter regions of microRNAs, known to be associated with cancer-related pathways like Wnt, ErbB, and PI3K-Akt signaling, were identified. Selected DMRs were confirmed in 2 independent patient cohorts. Inverse correlation between promoter methylation and expression suggested miR-129-2 and members of the miR-200 family (miR-200a, miR-200b, and miR-429) as novel tumor suppressors and oncomiRs, respectively, in CC. Tumor suppressor genes deleted in liver cancer 1 ( DLC1 ), F-box/WD-repeat-containing protein 7 ( FBXW7 ), and cadherin-6 ( CDH6 ) were identified as presumed targets in CC. Tissue microarrays of a representative and well-characterized cohort of biliary tract cancers (n=212) displayed stepwise downregulation of CDH6 and association with poor patient outcome. Ectopic expression of CDH6 on the other hand, delayed growth in the CC cell lines EGI-1 and TFK-1, together suggesting a tumor suppressive function of CDH6 . Our work represents a valuable repository for the study of epigenetically altered miRNAs in cholangiocarcinogenesis and novel putative, CC-related tumor suppressive miRNAs and oncomiRs.